2020
DOI: 10.1111/1471-0528.16149
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐urethral sling revision for mesh exposure–long‐term outcomes of two surgical techniques from a comparative clinical retrospective cohort study

Abstract: Objective To compare vaginal closure with versus without sling excision in the management of vaginal sling exposure following mid‐urethral sling (MUS). Design Clinical retrospective cohort study. Setting Tertiary urogynaecological centre in Australia. Population Women with urodynamic stress urinary incontinence (SUI) who had a MUS (n = 2823) during 1999–2017 with a follow‐up period up to December 2018. Thirty‐three women (1%) had sling exposure and 31 required surgical intervention (1%). Methods Clinical revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Karmakar et al. reported success rates of 95% when mid‐urethral sling mesh was partially excised in patients with mesh exposure 34 . It is unclear whether partial excision, as opposed to complete excision as performed in this study, would be as effective for patients with pain.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…Karmakar et al. reported success rates of 95% when mid‐urethral sling mesh was partially excised in patients with mesh exposure 34 . It is unclear whether partial excision, as opposed to complete excision as performed in this study, would be as effective for patients with pain.…”
Section: Discussionmentioning
confidence: 73%
“…Karmakar et al reported success rates of 95% when mid-urethral sling mesh was partially excised in patients with mesh exposure. 34 It is unclear whether partial excision, as opposed to complete excision as performed in this study, would be as effective for patients with pain. We also found that opioid use was high in this population and future studies will aim to describe opioid use in this study population in more detail.…”
Section: Research Implicationsmentioning
confidence: 85%
See 2 more Smart Citations
“…A total of 15 single-cohort studies of fair and poor quality evaluated mesh erosion preoperatively and postoperatively; 11 [17][18][19]22,[33][34][35][36][37][38]49 report on partial mesh removal, and four 3,43,45,50 report on total mesh removal. The single-group studies all implied resolution of mesh erosion postoperatively, but very few considered this a primary outcome, and postoperative statistics were lacking.…”
Section: Resultsmentioning
confidence: 99%